Effect of soluble calcium on enhancing nitrate retention by biochar. (15th November 2020) - Qin, Junhao; Niu, Anyi; Li, Qiwen; Liu, Yanqing; Lin, Chuxia
Abstract: Batch experiments were conducted to test the hypothesis that nitrate (NO3 − ) could be immobilized by biochar via adsorption of CaNO3 + to the negatively charged biochar surfaces. The results show that addition of soluble Ca in both aqueous and soil systems enabled NO3 − retention by the biochar material. Increase in the added Ca enhanced the retention rate and the optimal NO3 − retention was gained at a Ca/NO3 molar ratio of 2 for the aqueous system. For the soil system, the Ca/NO3 molar ratio required to attain the optimal NO3 − retention was much greater due to competition of other soil-borne ligands and soil colloids for the available Ca. At the same level of added Ca, the amount of NO3 − being retained tended to increase with increasing dose of the biochar. More NO3 − was retained in the soil system than in the aqueous system at the same dosage level of biochar due to additional adsorption of CaNO3 + by negatively changed soil organic and inorganic colloids. The findings obtained from this study have implications for developing effective methods for reducing NO3 − leaching from soils. Highlights: Addition of Ca enabled nitrate retention by the biochar material. This was via adsorption of by negatively charged biochar surfaces. Optimal nitrate retention at a Ca/NO3 molar ratio of 2 for aqueous system. Ca/NO3 ratio for optimal nitrate retention in soil was greater. Nitrate retention was enhanced by increasing dose of the biochar.